Modafinil and cognitive enhancement in schizophrenia and healthy volunteers: the effects of test battery in a randomised controlled trial. Issue 13 (3rd May 2017) - Lees, J.; Michalopoulou, P. G.; Lewis, S. W.; Preston, S.; Bamford, C.; Collier, T.; Kalpakidou, A.; Wykes, T.; Emsley, R.; Pandina, G.; Kapur, S.; Drake, R. J.
Abstract : Background: Cognitive deficits in schizophrenia have major functional impacts. Modafinil is a cognitive enhancer whose effect in healthy volunteers is well-described, but whose effects on the cognitive deficits of schizophrenia appear to be inconsistent. Two possible reasons for this are that cognitive test batteries vary in their sensitivity, or that the phase of illness may be important, with patients early in their illness responding better. Methods: A double-blind, randomised, placebo-controlled single-dose crossover study of modafinil 200 mg examined this with two cognitive batteries [MATRICS Consensus Cognitive Battery (MCCB) and Cambridge Neuropsychological Test Automated Battery (CANTAB)] in 46 participants with under 3 years' duration of DSM-IV schizophrenia, on stable antipsychotic medication. In parallel, the same design was used in 28 age-, sex-, and education-matched healthy volunteers. Uncorrected p values were calculated using mixed effects models. Results: In patients, modafinil significantly improved CANTAB Paired Associate Learning, non-significantly improved efficiency and significantly slowed performance of the CANTAB Stockings of Cambridge spatial planning task. There was no significant effect on any MCCB domain. In healthy volunteers, modafinil significantly increased CANTAB Rapid Visual Processing, Intra-Extra Dimensional Set Shifting and verbal recall accuracy, and MCCB social cognition performance. The only significant differences between groups were in MCCB visual learning. Conclusions: As in earlier chronic schizophrenia studies, modafinil failed to produce changes in cognition in early psychosis as measured by MCCB. CANTAB proved more sensitive to the effects of modafinil in participants with early schizophrenia and in healthy volunteers. This confirms the importance of selecting the appropriate test battery in treatment studies of cognition in schizophrenia.